2007
DOI: 10.1111/j.1600-9657.2006.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium ion diffusion from mineral trioxide aggregate through simulated root resorption defects

Abstract: The purpose of this study was to investigate the diffusion of calcium ions (Ca+2) through exposed dentinal tubules following intracanal application of mineral trioxide aggregate (MTA). Fifty-two single-rooted teeth were instrumented using 2.5% sodium hypochlorite for irrigation between each file size. Thereafter, standardized defects were created on the root surfaces so as to mimic external root resorption. The root canals and external defects received a final irrigation of 17% ethylenediaminetetraacetic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 24 publications
6
45
1
3
Order By: Relevance
“…Previous studies reported that the rate of calcium ion release of MTA was significantly compromised due to the presence of Bi 2 O 3 in its composition (6,7). However, various in vivo studies that assessed the biocompatibility of this cement (21,22) demonstrated that after 30 days, the material allowed adequate tissue repair, indicating that the alkaline pH produced by calcium ion release was maintained (22,23).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies reported that the rate of calcium ion release of MTA was significantly compromised due to the presence of Bi 2 O 3 in its composition (6,7). However, various in vivo studies that assessed the biocompatibility of this cement (21,22) demonstrated that after 30 days, the material allowed adequate tissue repair, indicating that the alkaline pH produced by calcium ion release was maintained (22,23).…”
Section: Discussionmentioning
confidence: 98%
“…In spite of various studies demonstrating the biocompatibility (3) and bioactivity (4,5) of MTA, bismuth oxide (Bi 2 O 3 ), the inorganic compound that provides radiopacity to the cement, interferes in its hydration mechanism (6), compromising calcium ions release to the tissue (7). Therefore, the formation of hard reparative tissues on exposed pulps and the formation of a complete mineralized barrier may be a negative influence of Bi 2 O 3 in the MTA composition (8).…”
Section: Introductionmentioning
confidence: 99%
“…The calcium ion release is enhanced when calcium chloride is added as an accelerator to MTA [ 12 ]. Moreover, when MTA was placed into the root canals of teeth with simulated radicular resorption, a greater calcium ion release was detected in comparison to teeth not fi lled with MTA [ 131 ].…”
Section: Introductionmentioning
confidence: 95%
“…MTA obturations in teeth with immature apices can induce apexo-genesis by stimulating the mesenchymal stem cells from the apical papilla to promote complete root maturation in the presence of periapical pathosis or abscesses [40] . Resorption : It has been shown that intracanal application of MTA can also cause release of calcium ions through dentinal tubules into External Resorption defect, which may halt the progress of resorption and favour repair potential of the surrounding tissues [41] . Recent research has demonstrated that root canal treated teeth obturated with MTA exhibit higher fracture resistance than their untreated counterparts [42] .…”
Section: Clinical Performance Studiesmentioning
confidence: 99%